Development, feeding, and sex shape the relative quantity of the nutritional obligatory symbiont Wolbachia in bed bugs - Poulain, Marius; Rosinski, Elodie; Henri, Hélène; Balmand, Séverine; Delignette-Muller, Marie-Laure; Heddi, Abdelaziz; Lasseur, Romain; Vavre, Fabrice; Zaidman-Rémy, Anna; Kremer, Natacha (Frontiers in Microbiology, 2024)
The common bed bug, Cimex lectularius, is a hemipteran insect that feeds only on blood, and whose bites cause public health issues. Due to globalization and resistance to insecticides, this pest has undergone a significant and global resurgence in recent decades. Blood is an unbalanced diet, lacking notably sufficient B vitamins. Like all strict hematophagous arthropods, bed bugs host a nutritional symbiont supplying B vitamins. In C. lectularius, this nutritional symbiont is the intracellular bacterium Wolbachia (wCle). It is located in specific symbiotic organs, the bacteriomes, as well as in ovaries. Experimental depletion of wCle has been shown to result in longer nymphal development and lower fecundity. These phenotypes were rescued by B vitamin supplementation. Understanding the interaction between wCle and the bed bug may help to develop new pest control methods targeting the disruption of this symbiotic interaction. The objective of this work was thus to quantify accurately the density of wCle over the life cycle of the host and to describe potential associated morphological changes in the bacteriome. We also sought to determine the impact of sex, feeding status, and aging on the bacterial population dynamics. We showed that the relative quantity of wCle continuously increases during bed bug development, while the relative size of the bacteriome remains stable. We also showed that adult females harbor more wCle than males and that wCle relative quantity decreases slightly in adults with age, except in weekly-fed males. These results are discussed in the context of bed bug ecology and will help to define critical points of the symbiotic interaction during the bed bug life cycle.